2018
DOI: 10.1371/journal.pone.0205554
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of narrow band imaging in the assessment of laryngeal papillomatosis

Abstract: Objectives/HypothesisRecurrent respiratory papillomatosis (RRP) is a benign disease caused by human papillomavirus 6 and 11. The characteristic feature of this disease are wart-like lesions covering the respiratory epithelium with a predilection for the larynx. There is no curative treatment for the disease. The goal of the treatment is a total surgical removal of the papillomatous lesions in order to reduce the number of relapses. Therefore, a good visualization method of papillomas is crucial during surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…They believe that narrowband imaging can improve the detection rate of laryngeal papilloma. [14][15][16][17][18] However, haemoglobin absorption spectral imaging based on similar imaging principles has not been reported. Therefore, we decided to systematically summarise and compare the microscopical haemoglobin absorption spectral imaging mode and the white light mode in evaluating papilloma lesions.…”
Section: Discussionmentioning
confidence: 99%
“…They believe that narrowband imaging can improve the detection rate of laryngeal papilloma. [14][15][16][17][18] However, haemoglobin absorption spectral imaging based on similar imaging principles has not been reported. Therefore, we decided to systematically summarise and compare the microscopical haemoglobin absorption spectral imaging mode and the white light mode in evaluating papilloma lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several authors have underlined the utility of NBI for detection of recurrent respiratory papillomatosis and its ability to increase the detection rate of small lesions that invisible by WL alone [29,33,[39][40][41][42]. The excellent performance in terms of CU + Ve and CU−Ve searching for wide angle IPCLs in the identification of respiratory papillomatosis mandates, as previously suggested by the recent literature [33,[39][40][41][42][43][44], the use of biologic endoscopy tools like NBI, and should be considered the endoscopic gold standard for optical biopsy and follow-up of patients affected by laryngeal papillomas.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found 27 patients with RRP (8.3%), 3 cases were initially suspected from malignancy and proved to be false positive. However, if RRP is suspected other synchronous papillomatous lesions (Jackowska et al 2018) can be detected in NBI. In our study NBI revealed other lesions not visible in WLE in 14/27 (51.8%) (20).…”
Section: Discussionmentioning
confidence: 99%